(3GdedJbW ef TQM GdhGMOi dTYQ GdeJfHis - (3CHi GdbGSe LGQGddg eMehO Hf YeQ Hf eMeO GdNhGQRei GdReNTQis; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s ((3eMeO Hf GdNVQ GdCfUGQi GdehUdi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdReNTQi gPG eG GdJbWJg ef TQM TYQ CHj GdWjH Yf GdhGMOi s
(3BNQgG (B:s
(3BNQ eG GTJed Ydjg OjhGfg GdPi QJHg HfaSg Je GdedJbW ef TYQ GdeJfHi Yf CHj GdMSf GdhGMOi GdJbWg GdReNTQi s
(3UaMI GdYfhGf ePgHIs
(3HChdgG JedcGJ CbOegG eDQN Sfg (B844(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
Keywords: (3GdCOHs